2006
DOI: 10.1021/jo060436i
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Reverse Anomeric Effect in Furanosides

Abstract: A series of conformationally restricted N-"furanosides" has been synthesized, where the carbons of the tetrahydrofuran ring are kept in one plane by a rigid norbornane skeleton, permitting only the ring oxygen to move above or below the tetrahydrofuran ring plane. This causes the substituents of the anomeric carbon to occupy a pseudoaxial or a pseudoequatorial position. On protonation of these "norbornane-furanosides" with trifluoromethanesulfonic acid, all three compounds exhibited decreasing coupling constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…In furanoses similar to the ones discussed in this work, an inverse anomeric effect has recently been excluded[39].…”
mentioning
confidence: 83%
“…In furanoses similar to the ones discussed in this work, an inverse anomeric effect has recently been excluded[39].…”
mentioning
confidence: 83%
“…[2][3][4][5] Subsequent investigations explored its theoretical basis to distinguish between cause and effect, through semi-empirical and ab initio calculations, 6,7 but many others questioned its realityand its definition. [8][9][10][11][12][13][14][15][16] Perrin et al for example, 11 discussed two different measures of the RAE, one based on the equilibrium between the normal ( 4 C 1 ) and inverted ( 1 C 4 ) conformers of the a anomer; the other on the equilibrium between the a and b anomers of the 4 C 1 conformers, which forms the basis for the definition of the normal anomeric effect. Based on the second measure and comparing solution equilibria between the a and b anomers of a series of D-glucosylamines 10 and subsequently, N-(glycopyranosyl) imidazole 12 and aniline 13 derivatives, Perrin et al found no evidence for a reversal of the normal anomeric effect.…”
Section: Introductionmentioning
confidence: 99%
“…[64] Is the RAE operative in other systems? [65] Does the RAE behave as as ynthetic control element? [66] If the RAE model is agood one,then these questions are meaningful, and dedication of mental and physical resources to their elucidation is productive.B ut in the more parsimonious scenario in which no RAE exists,these inquiries are distracting.…”
Section: Methodsmentioning
confidence: 99%